2023
DOI: 10.3390/microorganisms11030776
|View full text |Cite
|
Sign up to set email alerts
|

Colonization Ability of Bacillus subtilis NCD-2 in Different Crops and Its Effect on Rhizosphere Microorganisms

Abstract: Bacillus subtilis strain NCD-2 is a promising biocontrol agent for soil-borne plant diseases and shows potential for promoting the growth of some crops. The purposes of this study were to analyze the colonization ability of strain NCD-2 in different crops and reveal the plant growth promotion mechanism of strain NCD-2 by rhizosphere microbiome analysis. qRT-PCR was used to determine the populations of strain NCD-2, and microbial communities’ structures were analyzed through amplicon sequencing after applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Moreover, it has been shown that tomato, eggplant and pepper treated by B. subtilis NCD‐2 have significantly enhanced the plant height and biomass. Conversely, the same strain did only marginally affect the plant height of cotton and maize, suggesting species‐specific reactions (Zhao et al 2023), which fits well with our findings on the marginal growth promoting effects on wheat as compared to tomato. Thus, similar approaches generate different results in eudicots and monocots, highlighting the need to better understand and differentiate priming and prebiotic effects in different plant species to increase the efficiency and applicability of agricultural priming technologies for specific crops (Ortmann et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it has been shown that tomato, eggplant and pepper treated by B. subtilis NCD‐2 have significantly enhanced the plant height and biomass. Conversely, the same strain did only marginally affect the plant height of cotton and maize, suggesting species‐specific reactions (Zhao et al 2023), which fits well with our findings on the marginal growth promoting effects on wheat as compared to tomato. Thus, similar approaches generate different results in eudicots and monocots, highlighting the need to better understand and differentiate priming and prebiotic effects in different plant species to increase the efficiency and applicability of agricultural priming technologies for specific crops (Ortmann et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, rhizosphere colonization by arbuscular mycorrhizal fungi enhances resistance to pathogens [135] Apart from promoting plant growth, rhizosphere microbes regulate crop pests and diseases. However, it is crucial to recognize that some soil-dwelling microbes can harm animals and humans [136]. As a result, developing or screening microbial species for biotechnological applications or environmental remediation becomes crucial.…”
Section: Microbial Population Engineeringmentioning
confidence: 99%
“…Genetically engineered bacterial strains can synthesize rhizosphere molecules necessary for plants to extract vital nutrients from the soil. In a greenhouse experiment, researchers applied an engineered bacterial strain to the soil surrounding maize plant roots, resulting in a 40% reduction in the fertilizer input [136]. In arid regions worldwide, soil pH exhibits a wide range, from 5 to 10, and can even be lower than 5 in some areas, with conductivities below 200 µS/cm [21].…”
Section: Microbial Population Engineeringmentioning
confidence: 99%
“…Bacillus subtilis NCD-2 showed a promising biocontrol effect against plant soil-borne diseases and was developed as a commercial microbial fungicide against cotton verticillium wilt in China [15][16][17]. This study aimed to screen the nutrients suitable for the growth and sporulation of strain NCD-2 and then explore the mechanism for regulating sporulation via these nutrients.…”
Section: Introductionmentioning
confidence: 99%